Engagement as a Lever: The Impact of Talent Management on Turnover Intentions at Ghana's Lands Commission - Ofori Appiah, Salomey; Boateng, Richard kofi (Golden Ratio of Human Resource Management, 2025)
This study examined the moderation effect of employee engagement in the relationship between talent management and turnover intentions of workers at the Ghana Lands Commission. The study used the human capital and equity theories to explain the relationships among the constructs. The study used the quantitative approach and structural equation modelling (SEM) and employed structural equation modeling (SEM). Data was obtained from 300 employees using a three-wave survey approach that assured accuracy and reduced common method bias, resulting in a final sample of 250 respondents. The study found a positive significant effect of talent management on turnover intention. Again, employee engagement was found to significantly reduce employees’ intentions to quit, showing engagement's protective role against the potentially negative consequences of certain talent management practices. Finally, the study found engagement as a significant negative moderator on the link between talent management and turnover intentions. This emphasizes the need to cultivate a work environment that promotes participation, equality, and transparency in people management practices to reduce employee turnover and increase organizational stability.